2014
DOI: 10.1371/journal.pone.0094259
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular α-Synuclein Leads to Microtubule Destabilization via GSK-3β-Dependent Tau Phosphorylation in PC12 Cells

Abstract: α-Synuclein (ASN) plays an important role in pathogenesis of Parkinson's disease (PD) and other neurodegenerative disorders. Novel and most interesting data showed elevated tauopathy in PD and suggested relationship between ASN and Tau protein. However, the mechanism of ASN-evoked Tau protein modification is not fully elucidated. In this study we investigated the role of extracellular ASN in Tau hyperphosphorylation in rat pheochromocytoma (PC12) cells and the involvement of glycogen synthase kinase-3β (GSK-3β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 37 publications
0
55
0
Order By: Relevance
“…On the other hand, by decreasing Ser9 phosphorylation and elevating Tyr216 phosphorylation, ␣-Synuclein stimulates GSK-3␤ activity and inhibition of GSK-3␤ abrogates ␣-Synuclein mediated neurotoxicity (Fig. 2) [123]. In addition, GSK-3␤ also phosphorylates synphilin-1 (␣-Synucleininteracting protein) and decreases its ubiquitylation, mediated degradation [124], therefore it is suggested that this phosphorylation of synphilin-1/alpha-synuclein or direct activation of intrinsic cascades might be implicated in the GSK-3␤ induced toxicity [88].…”
Section: ˛-Synucleinmentioning
confidence: 99%
“…On the other hand, by decreasing Ser9 phosphorylation and elevating Tyr216 phosphorylation, ␣-Synuclein stimulates GSK-3␤ activity and inhibition of GSK-3␤ abrogates ␣-Synuclein mediated neurotoxicity (Fig. 2) [123]. In addition, GSK-3␤ also phosphorylates synphilin-1 (␣-Synucleininteracting protein) and decreases its ubiquitylation, mediated degradation [124], therefore it is suggested that this phosphorylation of synphilin-1/alpha-synuclein or direct activation of intrinsic cascades might be implicated in the GSK-3␤ induced toxicity [88].…”
Section: ˛-Synucleinmentioning
confidence: 99%
“…The kinases regulating phosphorylated (p)-tau include GSK3 [54,55], CDK5 [56], casein kinase 1 [54,55], PKA [54,55], p38 mitogen-activated protein kinase [57], SAPK4/p38 [58], and c-Jun N-terminal kinase families [59]. Previous studies have provided evidence that MPTP/MPP+ leads to the hyperphosphorylation of tau at Ser 396/404 both in vivo and in vitro by inducing a significant accumulation of α - Syn [7,60]. In an SH-SY5Y cell model of parkinsonism induced by MPP+, time- and dose-dependent increases in tau hyperphosphorylation at Ser 396/404 were observed [61].…”
Section: Discussionmentioning
confidence: 99%
“…GSK3, a major tau protein kinase, catalyzed and regulated tau phosphorylation at Ser 262 and Ser 396/404 [7,63,64,65]. The phosphorylation of GSK3β at Ser 9 or Tyr 216 was primarily targeted by the Akt signaling pathway [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular SelP binds to ApoER2, which initiates endocytosis and enables the selenocysteine supply. Presumably, in those conditions astrocytes are the main source of extracellular SelP, which in turn is taken up by neurons using the ApoER2 [57,33]. Aside from evidence that SelP serves to transport Se to brain tissue and to maintain its homeostasis, other suggesting function is a survival factor for neurons [58] as well as microtubule stabiliser.…”
Section: Selenoprotein Pmentioning
confidence: 99%